Mineralisaton assays of some organic resources of aquatic systems - BITAR,A. L. (2002)
Assays were carried out to evaluate the consumption of dissolved oxygen resulting from mineralisation processes in resources usually found in aquatic systems. They were also aimed at estimating the oxygen uptake rate of each investigated process. Experiments were conducted using substrates from 3 different places. A fixed amount of substrate was added to 5 litres of water from Lagoa do Infernão that was previously filtered with glass wool. After adding the substrates the bottles were aired and the amount of dissolved oxygen and the temperature were monitored for 55 days. The occurrence of anaerobic processes was avoided by reoxygenating the bottles. The experimental results were fitted to a first order kinetics model, from which the consumption of dissolved oxygen owing to mineralisation processes was obtained. The amount of oxygen uptake from the mineralisation processes appeared in the following decreasing order: Wolffia sp., Cabomba sp., Lemna sp., DOM (Dissolved Organic Matter), Salvinia sp., Scirpus cubensis, stem, Eichhornia azurea, sediment and humic compounds. The deoxygenation rates (day-1) were: 0.267 (humic compounds), 0.230 (Lemna sp.), 0.199 (E. azurea), 0.166 (S. cubensis), 0.132 (sediment), 0.126 (DOM), 0.093 (Cabomba sp.), 0.091 (stem), 0.079 (Salvinia sp. and Wolffia sp.). From these results, 2 groups of resources could be identified: the first one consists of detritus with higher amounts of labile (ready to use) compounds, which show a higher global oxygen uptake during the mineralisation process; the second one consists mainly of resources that show refracting characteristics. However, when the consumption rates are analysed it is noted that the mineralised parts of the refracting substrates can be easier to process than the labile fractions of the less refracting resources.